Geographic body size and shape variation in a mainland anolis (squamata: dactyloidae) from northwestern south america (colombia) (2014)
Anolis auratus is a widely distributed species, from Costa Rica in Central America, through northern South America, includingColombia, Venezuela, northern Brazil, Surinam and the Guyanas. In Colombia, its widespread distribution across different life zones suggests that these lizards occupy different environments and exhibit different microhabitat use in different geographic areas. On the other hand, some observations suggest that this species prefers open areas, selecting grasslands over brushy areas, and thus, an alternative hypothesis is that microhabitat use is similar among different populations. In Anolis, body variables related to locomotion (body size and shape) define structural microhabitat use, so two distinct patterns could be expected in this species: conservative or highly variable body size and shape throughout the species distribution. To test thesepredictions, we characterized geographic variation in morphometric traits of this species in Colombia. Females and males were similar in body size, but exhibited differences in some variables related to body shape. These characteristics also varied among males and females from different regions, suggesting heterogeneous use of structural microhabitat, between sexes and among populations. As an alternative, phylogenetic divergence among populations could also account for the observed differences. Absence of ecological and phylogenetic data limits our ability to identify the underlying causes of this pattern. However, we provide a general framework to explore hypotheses about evolution of body size and shape in this species.Variación geográfica en tamaño y forma corporalen un Anolis (Squamata: Dactyloidae) continentaldel noroeste de Suramérica (Colombia)RESUMENAnolis auratus se distribuye desde Costa Rica en Centro América, el norte de Sur América, incluyendo Colombia, Venezuela, norte de Brasil, Surinam y las Guyanas. En Colombia, su amplia distribución en distintas zonas de vida sugiere que estos lagartos ocupan distintos ambientes, y por tanto, posiblemente exhiben variación geográfica en el uso de microhabitat. Por otra parte, algunas observaciones sugieren que estos lagartos prefieren zonas abiertas, seleccionando pastizales y por tanto, una hipótesis alternativa es que usan el mismo microhabitat en toda su distribución. En Anolis, las variables corporales